THE SPREAD OF FOOT AND MOUTH DISEASE ON LIVESTOCK IN THE EX SEMARANG RESIDENCY 1981-1986: PENYEBARAN PENYAKIT MULUT DAN KUKU TERNAK DI EKS KARESIDENAN SEMARANG 1981-1986 - Dzikri Triyanto Ramadhan; Carolina Santi Muji Utami (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The spread of Foot and Mouth Disease (FMD) in livestock throughout the former Semarang Residency area from 1981-1986 was a disease that played a role in the history of Indonesian livestock farming. The outbreak began in Blora and quickly spread to neighboring areas, including Grobogan, Semarang, and Salatiga, due to inadequate biosecurity and the influx of imported infected animals. This study aims to understand how FMD impacted local livestock production and how the government responded to contain the epidemic. Using historical methods involving heuristics, source criticism, interpretation, and historiography, this study draws on archival documents, official reports, newspapers, and oral histories from affected farmers. The study findings reveal that FMD caused major disruptions in meat and milk production, economic losses for farmers, and public panic. In response, the government implemented mass vaccination programs, quarantine zones, and movement restrictions. A key outcome of these efforts was Indonesia’s official declaration as a FMD-free country in 1986, which was later recognized by international organizations. The novelty of this study lies in its historical perspective on veterinary crisis management and the strategic role of livestock policies during national emergencies, which offers some novelties in the history of foot and mouth disease in Indonesia.